Targeting colorectal cancer-associated bacteria: A new area of research for personalized treatments. (3rd July 2016) - Faïs, T.; Delmas, J.; Cougnoux, A.; Dalmasso, G.; Bonnet, R.
ABSTRACT: Most cases of colorectal cancer (CRC) are sporadic, and numerous studies have suggested that gut microbiota may play a crucial role in CRC development. Escherichia coli is a member of the gut microbiota frequently associated with colorectal tumors. CRC-associated E. coli strains frequently harbor the pks genomic island. This genomic island is responsible for the synthesis of colibactin genotoxin, which increases tumor numbers in CRC mouse models. We recently showed that targeting ClbP, a key enzyme involved in colibactin synthesis, blocks the deleterious effect of this toxin in vitro and leads to a significant decrease in tumor numbers in vivo . Altogether, our results suggest that the personalized treatment of CRC should also take into consideration the bacteria associated with the tumor in order to limit their deleterious effects.